The fifth man - Perry, Roland, 1946- (London : Sidgwick & Jackson, 1994)
Roland Perry has spoken to key players in M15 and the KGB, in London, Australia and Moscow in order to end decades of speculation about post-war British espionage. He reveals the identity of the'Fifth Man' - the man who assumed the legacies of Philby, Burgess, Maclean and Blunt.
Includes bibliographical references (pages [467]-468) and index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Rothschild, Nathaniel Mayer Victor Rothschild, -- Baron, -- 1910-; Spies -- United Kingdom -- Biography; Espionage, Soviet -- United Kingdom; Secret service -- United Kingdom